Altered stomatal dynamics in ascorbate oxidase over-expressing tobacco plants suggest a role for dehydroascorbate signalling - Fotopoulos, Vasileios; De Tullio, Mario C.; Barnes, Jeremy D.; Kanellis, Angelos K. (My University, 2008)
Control of stomatal aperture is of paramount importance for plant adaptation to the surrounding environment. Here, we report on several parameters related to stomatal dynamics and performance in transgenic tobacco plants (Nicotiana tabacum L., cv. Xanthi) over-expressing cucumber ascorbate oxidase (AO), a cell wall-localized enzyme of uncertain biological function that oxidizes ascorbic acid (AA) to monodehydroascorbic acid which dismutates yielding AA and dehydroascorbic acid (DHA). In comparison to WT plants, leaves of AO over-expressing plants exhibited reduced stomatal conductance (due to partial stomatal closure), higher water content, and reduced rates of water loss on detachment. Transgenic plants also exhibited elevated levels of hydrogen peroxide and a decline in hydrogen peroxide-scavenging enzyme activity. Leaf ABA content was also higher in AO over-expressing plants. Treatment of epidermal strips with either 1 mM DHA or 100 µM hydrogen peroxide resulted in rapid stomatal closure in WT plants, but not in AO-over-expressing plants. This suggests that signal perception and/or transduction associated with stomatal closure is altered by AO over-expression. These data support a specific role for cell wall-localized AA in the perception of environmental cues, and suggest that DHA acts as a regulator of stomatal dynamics.
Keywords: ABA; Apoplast; Ascorbic acid; Ascorbate oxidase; Dehydroascorbic acid (DHA); Hydrogen peroxide; Nicotiana tabacum L.; cv. Xanthi; Stomata; Transgenic plants; Water stress